From Overlooked to Unveiled: A Rare Case of Focal Jejunal Lymphangiectasia Presenting as Obscure Gastrointestinal Bleeding - Gayathri S. Menon; Shrivalli Nandikur; Prasanna S. Rao; Swarna Shivakumar; Aruna R. Patil (Journal of Gastrointestinal and Abdominal Radiology)
Intestinal lymphangiectasia (IL) is a rare disorder characterized by dilated lymphatic vessels within the small bowel wall. Focal IL is exceptionally uncommon, with gastrointestinal (GI) bleeding being a rare presentation. We report a case of a 50-year-old man presenting with recurrent melena and chronic iron deficiency anemia, in whom multiple endoscopic and radiological evaluations were initially inconclusive. Capsule endoscopy identified white punctate and plaque-like mucosal changes in the mid-jejunum, prompting a retrospective review of prior computed tomographic images, which uncovered a previously overlooked focal eccentric septate hypodense jejunal lesion. Surgical resection confirmed focal IL histologically. This case highlights the importance of a multidisciplinary approach and a high index of clinical suspicion in the evaluation of obscure GI bleeding, as focal IL is rare and may present with subtle imaging findings that are easily missed.